Measurement and Evaluation of the Online Marketing Training Results for Students at SMA Negeri 1 Bantur Malang - Arief Bustomi; Ali Yunus Rohedi; Muchamad Nurif (Institut Teknologi Sepuluh Nopember, 2021)
SMA Negeri 1 Bantur Malang is located in the southern area of Malang Regency. The demographic conditions and the Bantur community characteristics have caused many SMA Negeri 1 Bantur graduates to choose to work rather than continue their education to higher education. As a solution to this condition, the school has provided job training to students for one year as a provision for them after graduation. Apart from being in the form of student knowledge and skills, job training activities also produce goods and services that can be marketed to the public. Therefore, after participating in the training activities, SMA Negeri 1 Bantur students need to also be given training in marketing goods and services. This paper presents the results of online marketing training for goods and services at SMAN 1 Bantur. The method used in the training is tutorial and practice using text and video media. Measuring the success of training activities using the questionnaire method and assessment of the training participants' practice results. The results of measuring the success of training and their evaluation can measure the increase in knowledge and skills of each student who participates in the training.